The correlation of mother's knowledge, mother's attitude, and low birth weight (LBW) with stunting in toddlers at Kulon Progo District, Yogyakarta - Ghilari, Yampa Eksa Daidella (BKM Public Health and Community Medicine, 2021)
Objective : This study explores public health issues regarding toddlers of age 0-59 months, the most parental education is high school with job as housewife to prove the correlation of mother`s knowledge, mother`s attitude, and LBW with stunting in toddlers at Kulon Progo District, Yogyakarta in 2019. Method : This type of research was observasional analytic used cross-sectional study. Respondents of this study were children aged 0-59 months where stunting cases were found, there are five subdistricts: Galur, Sentolo, Pengasih, Nanggulan, and Samigaluh with a sample of 729 respondents with total sampling. Data collecting used primary data obtained from questionnaire and secondary data collection from KMS and record data by primary health care in 2019. Analyze data used chi-square test for bivariate and logistic regression analyze for multivariate. Results : The prevalence of stunting among under-five age of children in Kulon Progo district was 37,59%. There was a significant association between mother`s knowledge with stunting (p= 0,000 ; RP= 2,009 ; CI 95%= 1,64-2,45). There was a significant association between mother`s attitude with stunting (p= 0,000 ; RP= 2,29 ; CI 95%= 1,84-2,84), LBW was not necessarily a stunting risk in this study (p= 0,066; RP= 1,25 ; CI 95%= 0,97-0,62). The most affected variable with stunting is mother’s ettitude (OR= 3,297). Conclusion : There was a significant correlation between mother`s knowledge, mother`s attitude with stunting in Kulon Progo district, Yogyakarta in 2019. Improving women's nutrition, child feeding practices and household sanitation to help reduce stunting.